Optimizing the Quality of MSME Products: KKN 72 UINSA's Assistance to Alza Chips through Legality, Rebranding, and Digital Marketing - Alfani, Mukhammad; Rahmawati, Aisha; Yanti, Elly Rahmah; Salsabila, Jihan Nazila; Afandi, Putri Galuh; Sari, Silvi Nur Laila; Lusiana, Nova (Universitas Ibn Khaldun, 2024)
Business legality is really needed, especially for MSMEs, so that their business has an identity and can make all business permits easier. The aim of this community service is to improve the quality of MSME products through legality, rebranding, and digital marketing. The method used in the process of implementing this service is the ABCD (Asset Based Community Development) method. The ABCD method is a technique for finding and recognizing a community's capabilities so that it can manage its assets, strengths and potential. The results of this service are assistance with business legality through creating NIB, rebranding logos and packaging, and carrying out digital marketing by making promotional videos and registering production sites on Google Maps. Assistance activities for making NIB, product rebranding and digital marketing ran smoothly and had a good impact on improving the quality of the Alza chips business products.